2019
DOI: 10.1021/acs.orglett.9b02075
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Structural Revision of Monocillin VII

Abstract: The first asymmetric total synthesis of macrolactone monocillin VII and its C-10′ epimer was achieved starting from a known chiral pure epoxide in 16 longest linear sequences. The present synthesis highlights the macrolactone formation involving an alkyne−dicobalt carbonyl complex under De Brabander's conditions followed by an unexpected regioselective hydration. The asymmetric total synthesis resulted in the revision of the configuration at C10′ and reassignment of the absolute configuration of the natural pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…SC0924 79 which has antitumor activities (Scheme 40). 80 Treatment of lactone 67 with Ph 3 PAuCl/AgOTf in dioxane/ H 2 O delightfully gave β-ketone 68 with total β-regioselectivity in an excellent yield of 84%. The intramolecular assistance of the lactone function for the hydration reaction plays a key role in the achieved regioselectivity.…”
Section: Hydration Of Alkynes Directed By An Ester Functionmentioning
confidence: 99%
“…SC0924 79 which has antitumor activities (Scheme 40). 80 Treatment of lactone 67 with Ph 3 PAuCl/AgOTf in dioxane/ H 2 O delightfully gave β-ketone 68 with total β-regioselectivity in an excellent yield of 84%. The intramolecular assistance of the lactone function for the hydration reaction plays a key role in the achieved regioselectivity.…”
Section: Hydration Of Alkynes Directed By An Ester Functionmentioning
confidence: 99%
“…The synthesis of fragment 9 commenced from an advanced intermediate trans -2,6-disubstituted dihydropyran 12 which was synthesized in turn from a known chiral epoxide 13 12 (which was prepared from readily available starting material 3-buten-1-ol in three-step sequence, p -methoxybenzylation with PMB chloride, epoxidation with m CPBA followed by Jacobsen’s hydrolytic kinetic resolution (HKR) 13 using ( S , S )-Jacobsen catalyst in 43% yield and 98% ee (determined by chiral HPLC)) using a three-step protocol developed previously by our group in a 99:1 diastereomeric ratio. 11a d Next, following Jin’s one-step dihydroxylation–oxidation protocol, 14 terminal olefin was selectively oxidized to aldehyde followed by reduction with NaBH 4 in MeOH at 0 °C, which furnished the corresponding alcohol 14 in 78% yield over two steps. The alcohol 14 was protected with TBSCl in the presence of imidazole and a catalytic amount of DMAP in CH 2 Cl 2 at 0 °C to give compound 15 in 96% yield.…”
Section: Table 1 Screening Of Dihydroxylation Reaction ...mentioning
confidence: 99%
“…The structure–activity relationships analysis indicated that the acetoxy and acetonide groups at C5′–C6′ had positive effects on the antiplasmodial activity (Zhang et al 2017 ). Recently, total syntheses of paecilomycins E (Reddy et al 2019 ) and F, cochliomycin C, 6-epi-cochliomycin C (Kadari et al 2018 ), monocillin VII (Mallampudi et al 2019 ), 5′-hydroxyzearalenone, 5′β-hydroxyzearalenone (Thiraporn et al 2017 ), L-783290, L-783277 (Chakraborty et al 2020 ), paecilomycin B, 6′-epi-paecilomycin B (Ohba and Nakata 2018 ), zeaenol, and 7-epi-zeaenol (Doda et al 2019 ; Mohapatra et al 2014 ) were accomplished and reported. Given their intriguing antifouling and antiplasmodial properties and attractive chemical structures, this family of macrolides has attracted a growing interest in the fields of medicinal chemistry and organic chemistry.…”
Section: Introductionmentioning
confidence: 99%